Employee Outcomes of Effective Internal Communication: A Case Study of Manufacturing Firm in Thailand - Duangekanong, Duangta; Jittawiriyanukoon, Chanintorn; Duangekanong, Somsit (NIDA Development Journal, 2018)
The purpose of this research is to examine internal communication quality on employee outcomes including organizational commitment and job satisfaction in a manufacturing firm. Objectives include establishing a theoretical model of causes and consequences of internal communication. The study has been conducted as an online survey of employees within the organization, including managerial and non-managerial employees, with analysis conducted using structural equation modeling (SEM). The analysis shows that social acceptance of communication (appropriateness and acceptability) influenced perceptions of two dimensions of communication quality (flow and content). Perceptions of organizational communication structure, flow, content, and climate positively influenced internal communications quality perceptions, while employee resistance to change negatively influenced internal communications quality perceptions. The study also demonstrates that internal communications quality is thus positively associated with commitment and satisfaction while negatively associated with continuance commitment. The implication of this research is that internal communications research needs to examine employee characteristics more thoroughly.